Physiology for the pulmonary functional imager. Issue 86 (January 2017) - Levin, David L.; Schiebler, Mark L.; Hopkins, Susan R.
Highlights: An understanding of the relevant pulmonary physiology is crucial to functional lung imaging. Spatial resolution for pulmonary functional imaging can be substantially less than that used for anatomic/clinical imaging. Regional deformation of the lung under the influence of gravity significantly affects the measurement of pulmonary perfusion. Large vessels identified on perfusion imaging do not represent local blood flow. Pulmonary diseases are typically characterized by a change in the matching of ventilation and perfusion. Abstract: As pulmonary functional imaging moves beyond the realm of the radiologist and physicist, it is important that imagers have a common language and understanding of the relevant physiology of the lung. This review will focus on key physiological concepts and pitfalls relevant to functional lung imaging.